2017
DOI: 10.1111/let.12198
|View full text |Cite
|
Sign up to set email alerts
|

The post‐Palaeozoic fossil record of drilling predation on lingulide brachiopods

Abstract: Research on drilling predation, one of the most studied biological interactions in the fossil record, has been concentrated on prey with calcareous skeletons (e.g. molluscs, echinoids, rhynchonelliform brachiopods). Based on a compilation of literature sources and surveys of paleontological collections of the Florida Museum of Natural History and the National Museum of Natural History, we provide a tentative evaluation of the post‐Palaeozoic history of drilling predation on the organophosphatic brachiopods of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 59 publications
0
4
1
Order By: Relevance
“…Concerning the infaunal species Gresslya intermedia from the upper Pliensbachian ( Amaltheus margaritatus Zone and Pleuroceras spinatum Zone), SPPAT shows a concentration of drill holes on the central shell region. In contrast with a previous study of predation by naticid gastropods on bivalve prey (Rojas et al 2015, 2020), distance-based statistics do not support segregated patterns. The central shell region in Gresslya represents the region with more inflation and also the region where most soft tissues (gonads, stomach) were probably located, while the posterior region was mostly filled with the siphon.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Concerning the infaunal species Gresslya intermedia from the upper Pliensbachian ( Amaltheus margaritatus Zone and Pleuroceras spinatum Zone), SPPAT shows a concentration of drill holes on the central shell region. In contrast with a previous study of predation by naticid gastropods on bivalve prey (Rojas et al 2015, 2020), distance-based statistics do not support segregated patterns. The central shell region in Gresslya represents the region with more inflation and also the region where most soft tissues (gonads, stomach) were probably located, while the posterior region was mostly filled with the siphon.…”
Section: Discussioncontrasting
confidence: 99%
“…Although there is a substantial amount of drill-hole record from the Cretaceous onward (Huntley and Kowalewski 2007; Rojas et al 2017), the record is quite scarce in the Triassic (i.e., Fürsich and Jablonski 1984; Newton et al 1987; McRoberts and Blodgett 2000; Klompmaker et al 2016; Tackett and Tintori 2019) and in the Jurassic (i.e., Sohl 1969; Bromley 1981; Harper et al 1998; Kowalewski et al 1998; Harper and Wharton 2000; Aberhan et al 2011; Bardhan et al 2012; Karapunar et al 2020a,b; Saha et al 2021; see also Fürsich et al 2023). Different hypotheses have been proposed to explain the rarity of drill holes in the Mesozoic fossil record: low diversity of drilling organisms (Kowalewski et al 1998; Huntley and Kowalewski 2007), low sampling intensity and poor preservation (Huntley and Kowalewski 2007), and taphonomic bias (Harper et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Drilling predation on shelled marine invertebrates represents a unique opportunity to quantify biological interactions in ancient and modern marine environments. Predatory drillholes represent direct records of predatory attack and can potentially document diverse aspects of predator–prey interactions (e.g., Kitchell et al 1981; Kitchell 1986; Dietl and Alexander 2000; Kowalewski 2002; Hoffmeister et al 2004; Rojas et al 2017), although several assumptions and caveats need to be considered (e.g., Kowalewski 2002; Leighton 2002; Harper 2006; Klompmaker et al 2019; Smith et al 2019). Drillholes can provide valuable behavioral information regarding selectivity of predatory attacks in terms of prey species, prey size class, or drilling location on the prey skeleton (e.g., Kitchell 1986; Kowalewski 2002).…”
Section: Introductionmentioning
confidence: 99%
“…1). More recently, studies of predation in deep time have evaluated macroevolutionary effects of predation (e.g., Dietl and Kelley, 2002;Huntley and Kowalewski, 2007;Jablonski, 2008;Nagel-Myers et al, 2013;Roy, 1996), documented predation on taxa that had not been identified as viable prey or were previously largely overlooked in the fossil record (e.g., Baumiller, 1996Baumiller, , 1990Baumiller and Bitner, 2004;Bicknell et al, 2018;Gordillo, 2013a;Klompmaker, 2012Klompmaker, , 2011Klompmaker et al, , 2014Klompmaker et al, , 2013Kowalewski et al, 2005;Rojas et al, 2017Rojas et al, , 2014, and explored geologic times and geographic localities that are relatively less known for their predation record (e.g., Chattopadhyay and Dutta, 2013;Kowalewski et al, 2000Kowalewski et al, , 1998Mallick et al, 2017;Morris and Bengtson, 1994;Villegas-Martín et al, 2016). Many of these studies established temporal trends in predation by compiling data from the existing literature or by processing bulk samples to develop large-scale datasets on predation traces (e.g., Huntley and Kowalewski, 2007; Kelley…”
Section: History and Types Of Studiesmentioning
confidence: 99%
“…Mollusks tend to possess more soft tissue than similar-sized brachiopods (Peck, 1993), so that a drill hole in a mollusk is more likely to be predatory than parasitic (but see capulids). Conversely, drill holes in brachiopods have been variously interpreted (Baumiller et al, 2006(Baumiller et al, , 1999Daley, 2008;Harper and Wharton, 2000;Hiller, 2014;Rojas et al, 2017;Schimmel et al, 2012). Compared to mollusks, most crinoids contain little soft tissue (Baumiller, 2003b), and these echinoderms were infested by parasitic…”
Section: Predatory Versus Parasitic Tracesmentioning
confidence: 99%